Protein quality control in the cytosol and the endoplasmic reticulum: brothers in arms - Buchberger, Alexander; Bukau, Bernd; Sommer, Thomas (Molecular cell, 2010)
In cells, both newly synthesized and pre-existing proteins are constantly endangered by misfolding and aggregation. The accumulation of damaged proteins can perturb cellular homeostasis and provoke aging, pathological states, and even cell death. To avert these dangers, cells have developed powerful quality control strategies that counteract protein damage in a compartment-specific way. Here, we compare the protein quality control systems of the eukaryotic cytosol and the endoplasmic reticulum, focusing on the principles of damage recognition, the triage decisions between chaperone-mediated refolding and proteolytic elimination of damaged proteins, the repair of misfolded and aggregated protein species, and the mechanisms by which perturbations of protein homeostasis are sensed to induce compartment-specific stress responses.
Gesehen am 09.03.2023